Carbon stock and growth performance of different kenaf (Hibiscus cannabinus L.) varieties in bris soil of different organic carbon levels - Hossain, Md. Delwar (2012)
High interest in growing kenaf throughout the world is due to its high biomass yield, elevated fiber contents, and as good carbon (C) sequesters plant. Soil fertility management is a pre-requisite for successfully growing kenaf in marginal soil. Hence, the overall objectives were (i) to determine the optimum levels of N, P, and K for optimum growth of kenaf, (ii) to evaluate the effects of different C levels and sources on the growth, biomass production, physiological traits, fiber yield, fiber morphological traits and C stock by the kenaf plants and soil, (iii) to study the root characteristics of kenaf varieties and to relate the shoot growth to root traits of different varieties, and (iv) to determine the effects of C levels on kenaf under field conditions. The optimum levels of major nutrients, N, P, and K, were obtained by growing V36 kenaf variety in polypropylene trays containing aerated Hoagland’s nutrient solution using five different concentrations. Plants grown under N, P, and K deprivation showed significantly lower growth, biomass production, chlorophyll content, photosynthesis and stomatal conductance. The highest values for these parameters were obtained from 200 N, 100 P, and 100 K (in mg L-1) and then declined. The effects of different C levels and sources on the growth, biomass production, physiological traits, fiber yield, fiber morphological traits and C stock by the kenaf plants and soil were evaluated in the glasshouse. The maximum values of these parameters were achieved at 20 t ha-1 C level. The variety HC2 accumulated the highest dry matter followed by V36. Most of the dry matter accumulation occurred in stems (63.98%). Of the five varieties, the average dry matter in stems was 76.83% and in leaves was 20.56%. The macro- and micro-nutrients proportion varied markedly in plant components and varieties. The kenaf varieties exhibited significant variation in fiber length, width, lumen width, and cell wall thickness. The maximum C stock was observed for variety HC2 and at 20 t ha-1 C level. The root growth, total root length, number of root tips, root surface area and root volume showed significant differences in their responses to C levels in pot experiment. The varieties, producing higher shoot growth, were associated with the higher values of root traits. The effects of C levels on kenaf were investigated under natural field condition for two seasons. Kenaf plants cannot generate vigorous plants growth under zero C level. The differences in plant growth, physiological parameters, proportions of macro- and micronutrients and total nutrients accumulated in the plant components, yield, fiber morphological dimensions and C stock suggested that the variety HC2 as well as V36 could be considered as the appropriate varieties to be grown on BRIS soil under effective management of organic C.